Penurunan Tekanan Darah pada Pasien Hipertensi Menggunakan Intervensi Slow Deep Breathing Exercise - Juli Andri; Fahri Permata; Padila Padila; Andry Sartika; Muhammad Bagus Andrianto (Jurnal Keperawatan Silampari, 2021)
This study aims to determine the effect of slow deep breathing exercise on reducing blood pressure in hypertensive patients in the Telaga Dewa Health Center work area, Bengkulu City. This research method is quantitative research with a quasi-experimental research design. The results of univariate analysis obtained that the average respondent was 64 years old, with the majority gender being female, namely seven respondents (53.3%). Most respondents have a family history of hypertension, as many as 12 respondents (80%). The results of the bivariate analysis showed that the p-value <0.05. In conclusion, there is a decrease in systolic and diastolic blood pressure before and after slow deep breathing intervention in hypertension sufferers in the Telaga Dewa Health Center Work Area, Bengkulu City. Keywords: Hypertension, Slow Deep Breathing Exercise, Blood Pressure